Efektivitas teknik bermain peran untuk meningkatkan kepercayaan diri siswa - Anna Rufaidah; Dian Renata; Christine Masada (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2019)
This Study aims to reveal how much self-confidence of student increase after learning with role play techniques. The method used is an experimental method with a quantitative approach the randomized pretest-posttest control group design. Meanwhile, it involved 78 subjects chosen through simple random sampling technique from 94 students. Based on the results of study can be put forward some conclusions as follows: the level of student confidence based on the results of the pretest is in the low category. After being treated in the form of role playing techniques aimed at changing from low self confidence to high categories. The result showed that role playing techniques wre effective to increasing student confidence